Literasi Media Dalam Menanggulangi Berita Hoax Di Media Sosial Mahasiswa Ilmu Perpustakaan - Rizkiyatun Fadillah Lubis; Abdul Karim Batubara; Indira Fatra Deni P (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2023)
This study aims to determine the ability of Library Science students to analyze hoax news on social media, the ability of Library Science students to access hoax news on social media, the relationship between the media literacy skills of Library Science students in tackling hoax news on social media, and the ability of Library Science students to evaluate news. hoaxes on social media. This study uses quantitative research using a questionnaire as a means of collecting data obtained from respondents. The population of this study were all Library Science students of UIN North Sumatra from the 2019 stambuk, 2020 and 2021, namely 352 students with a total sample of 79 students determined by the slovin formula. The sampling technique used to determine the sample is Random Sampling/Probability Sampling. To measure the relationship between the media literacy abilities of Library Science students at UIN North Sumatra in tackling hoax news on social media and test hypotheses using the Spearman's Rho Rank-Order Correlations formula and Guilford's calculations. The results showed that media literacy ability had a positive relationship with a value of 0.358 which indicated a strong enough relationship in tackling hoax news.